Synthesis and Antibacterial Activity of 4-(4-Methylpent-3-enyl)cyclohex-4-ene-1,2-dicarboxamide - Lian, Jianwei; Xia, Jianling; Wang, Mei; Tang, Xiaodong; Gao, Lisha; Yang, Yafeng (Asian Journal of Chemistry, 2013)
In this paper, 4-(4-methylpent-3-enyl)cyclohex-4-ene-1,2-dicarboxamide was synthesized by b-myrcene through Diels-Alder reaction and ammonolysis reaction. The synthetic compound was proved to be the target product with the help of NMR, FT-IR and GC-MS. Diels-Alder reaction has been optimized under the following conditions: 150 ºC, reacting for 3 h, no catalyst and the production rate of 4-(4-methylpent-3-enyl)cyclohex-4-ene-1,2-dicarboxamide is 88.12 %, the selectivity is 97.49 %. Then get down to ammonolysis reaction under 0.4 MPa ammonia pressure for 18 h with methanol as the solvent and the production rate turned up to 88.7 %. At last, the test of the antibacterial activity of the target product showed optimistic to Staphylococcus aureus but passimistic to Escherichia coli.